2012
DOI: 10.1189/jlb.0911488
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar macrophages in diabetes: friends or foes?

Abstract: AMs constitute an important bridge between innate and adaptive immunity. AMs patrol the lungs against pathogens, remove senescent cells, and help repair tissue. AM function is altered in many diseases, including DM, where AM abnormal immune responses may worsen infections or lead to exacerbation of inflammatory reactions. In vivo experimental models have greatly contributed to our knowledge of AM function. Studies have shown that during hyperglycemic states, the phagocytic function of AMs and the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
0
10
0
2
Order By: Relevance
“…Alveolar macrophages from normal hosts demonstrate an aberrant immune response that contributes to worsening infection and autoimmunity when exposed to elevated glucose concentration [ 28 ]. Insulin resistance was detected two days prior to the clinical suspicion of ventilator-associated pneumonia for critically injured patients on the glycemic control protocol [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar macrophages from normal hosts demonstrate an aberrant immune response that contributes to worsening infection and autoimmunity when exposed to elevated glucose concentration [ 28 ]. Insulin resistance was detected two days prior to the clinical suspicion of ventilator-associated pneumonia for critically injured patients on the glycemic control protocol [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β is a pivotal inflammatory mediator, produced by PAMPs (Pathogen-associated molecular patterns)-activated cells of innate immune system, driving the host response to control infection or lead to tissue injuries [40]. Higher mRNA expression levels of IL-1β, MCP-1, and TNF-α have been demonstrated in the alveolar macrophages (AMs) of diabetic patients that failed to control infection in contrast to normal AMs [41]. Therefore, the lasting production of IL-1β, probably released by K. pneumoniae -activated Kupffer cells or neutrophils, might contribute to the enhancement of liver injury by diabetes (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence suggests that the abnormally high number of inflammatory cells in adipose tissue of obese subjects and type 2 diabetes patients may promote systemic inflammation and a microenvironment favorable for neoplastic cell survival and proliferation. For instance, aberrant alveolar macrophages contribute to worsening lung infection and autoimmunity in type 2 diabetes patients (Sunahara & Martins 2012). Fritz et al (2011) have recently demonstrated that alveolar macrophages release IGF1, which stimulates neoplastic mouse lung cell proliferation through PI3K/Akt and MAPK/ERK activation.…”
Section: Insulin Resistance Immune Response Alterations and Cancer:mentioning
confidence: 99%